Reliability of high-alert medications questionnaire in Turkish healthcare professionals - ALTIPARMAK, ÖZNUR; SANCAR, MESUT; OKUYAN, BETÜL (My University, 2022)
Objective: This study aimed to evaluate the reliability of the HighAlert Medications (HAM) Questionnaire in Turkish healthcare professionals. Methods: This methodological study was conducted between December 2017 and January 2018 in a private university hospital. The healthcare professionals, including nurses, health service technicians, and pharmacists, who are older than 18 years old were eligible for this study. After following the appropriate translation and cultural adaptation process, the internal consistency of the HAM Questionnaire using the Kuder-Richardson 20 coefficient and test-retest reliability was evaluated. Results: Among 146 healthcare professionals, the mean age was 25.40±5.16 years, wherein 76% were females. Most participants were nurses (69.9%) and other healthcare professionals were health service technicians (28.1%) and pharmacists (2.0%). The mean total score of the HAM Questionnaire was 70.00±19.50. The KuderRichardson 20 was 0.815. A statistically significant correlation was found between the scores of the HAM Questionnaire at baseline and after 15 days, which confirmed the test-retest reliability (r=0.527; p<0.01). A statistically significant correlation was found between the HAM Questionnaire score and advanced age (r=0.310; p<0.001) and higher professional year (r=0.445; p<0.001). Conclusion: The Turkish version of the HAM Questionnaire could be used to assess healthcare professionals’ knowledge about highalert medications.

Amaç: Sağlık çalışanlarında Yüksek Riskli İlaç Bilgi Anketi'nin anketinin güvenilirliğinin değerlendirilmesi amaçlanmaktadır. Yöntemler: Bu metodolojik çalışma Aralık 2017 ile Ocak 2018 tarihleri arasında özel bir üniversite hastanesinde gerçekleştirilmiştir. Çalışmamıza 18 yaşından büyük hemşireler, sağlık teknisyenleri ve eczacılar dahil edilmiştir. Uygun çeviri ve adaptasyon sürecini takiben, Kuder-Richardson 20 katsayısı kullanılarak yüksek riskli ilaçlar hakkında bilgi anketinin iç tutarlılığı ve test-tekrar test güvenilirliği değerlendirilmiştir. Bulgular: Çalışmamıza dahil edilen 146 sağlık çalışanının yaş ortalaması 25,40±5,16 olarak hesaplanmış ve katılımcıların %76’sı kadındır. Katılımcıların meslekleri, hemşire (%69,9), sağlık teknisyenleri (%28,1) ve eczacıdır (%2). Sağlık Çalışanlarında Yüksek Riskli İlaç Bilgi Anketi'nin toplam puan ortalaması 70,00±19,50 olarak hesaplanmıştır. Anket güvenilirliği için Kuder Richardson 20 değeri 0,815 olarak bulunmuştur. Testretest güvenilirliğini doğrulamak için, başlangıçta ve 15 gün sonra Yüksek Riskli İlaç Bilgi Anketi puanları arasında istatistiksel olarak anlamlı bir korelasyon bulunmuştur (r=0,527; p<0,01). Sağlık Çalışanlarında Yüksek Riskli İlaç Bilgi Anketinin puanı ile ileri yaş (r=0,310; p<0,001) ve mesleki tecrübe yılı (r=0,445; p<0,001) arasında istatistiksel olarak anlamlı bir korelasyon bulunmuştur. Sonuç: Sağlık Çalışanlarında Yüksek Riskli İlaç Bilgi Anketinin Türkçe versiyonu sağlık çalışanlarının yüksek riskli ilaçlar hakkındaki bilgilerini değerlendirmek için kullanılabilir.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; High-risk medication; healthcare professional; medication safety; pharmacist; nurse; knowledge; NURSES KNOWLEDGE; PRESCRIPTION; INSTRUMENT; Yüksek riskli ilaçlar; sağlık çalışanları; ilaç güvenliği; eczacı; hemşire; bilgi seviyesi; High-risk medication; healthcare professional; medication safety; pharmacist; nurse; knowledge